Perceptions of the corporate identity management process in South Africa - G. Bick; R. Abratt; A. Bergman (South African Journal of Business Management, 2008)
This article reports on a qualitative study of how the corporate identity management process is perceived and managed by senior executives in large South African companies. The concepts of identity, corporate reputation, corporate branding, and the corporate identity management process are discussed. It is suggested that these concepts create confusion among executives and academics and therefore the image and reputation of a company may be affected. Results are reported from an in-depth study of 14 senior managers and directors from 8 large companies. Key recommendations are made and a step-by-step guide is given on how to develop an effective and successful corporate identity, leading to a good reputation in the long term.
Keywords: 650